Blockbuster Performances How Actors Contribute to Cinema's Biggest Hits - Smith-Rowsey, Daniel (Palgrave Studies in Screen Industries and Performance, 2018)
This book examines performances in the American film industry's highest-earning and most influential films. Countering decades of discourse and the conventional notion that special effects are the real stars of Hollywood blockbusters, this book finds that the acting performances in these big-budget action movies are actually better, and more genre-appropriate, than reputed. It argues that while blockbusters are often edited for speed, thrills, and simplicity, and performances are sometimes tailored to this style, most major productions feature more scenes of stage-like acting than hyper-kinetic action. Knowing this, producers of the world's highest-budgeted motion pictures usually cast strong or generically appropriate actors. With chapters offering unique readings of some of cinema's biggest hits, such as The Dark Knight, Pirates of the Caribbean, Star Wars, Iron Man and The Hunger Games, this unprecedented study sheds new light on the importance of performance in the Hollywood blockbuster. .